Aprovisionamento avançado de recursos em redes convergentes sensíveis ao contexto - Cruz, Elifranio Alves (2012)
Due to the increase demand of mobile users for content created in a specific and customized way, or adapted to comply with the needs and preferences in web usage, converged networks which are context-sensitive have been incorporated to a promising technology and enabled applications of personalized services to multiple users. The C-CAST project (Context Casting) was established to converged network architectures to support context-sensitive sessions with quality of service (QoS - Quality of Service) in a manner to guarantee to multiple users simultaneously, regardless of their wireless technologies. The C-CAST control mechanism of the Legacy introduces issues of performance degradation, once the signaling approach adopted is directed per-flow, which means that the signaling load increases exponentially with the number of admissions flow. This work proposes the Advanced of C-CAST, which reconstruct the C-CAST legacy system by the extent of innovative mechanisms that integrate dynamic control of provisioned bandwidth by the service classes and allocation overlay trees. Through this strategy, it seeks to reduce rates of control signaling and allocating resources throughout the system. The C-CAST Advanced evaluation is conducted through simulation, demonstrating its benefits in relation to C-CAST Legacy, by significantly optimization the performance levels of the entire network system while keep the network users with the best quality perception.